POLA PEMBENTUKAN KARAKTER RELIGIUS BAGI SISWA DI SD AL-IRSYAD AL-ISLAMIYYAH MALANG - Rarasati, Ida Putri; Rosyida, Desy Anindia; Sari, Dea Ayu Belinda (Transpublika Publisher, 2022)
The purpose of this research is to find out how students at SD Al-Irsyad Al-Islamiyah Malang develop their religious identities during the course of their education. This study is an example of descriptive qualitative research, and it was conducted by selecting grades 1 to 6 as samples and talking to two informants, namely the principal and homeroom teachers of grades 1 to 6, both of whom are regarded as having knowledge and information about the issues that were researched, specifically the Pattern of Religious Character Formation for Students at SD AL -IRSYAD AL-ISLMAIYYAH MALANG. In-depth interviews with various informants were also part of the data collection process, in addition to the use of observation and documentation as data collection tools. A qualitative analysis was performed on the data. By conducting interviews with informants who were seen from the perspective of the influence of educators, students, canteens, classrooms, and playing fields, this study was able to show that quite good results were achieved in shaping the religious character of students. These results were shown in the findings of the study. The instructors as well as the students themselves each have a beneficial and a negative impact on the religious character that is developed in the kids.